Unraveling the Thermodynamics of Ultra-tight Binding of Intrinsically Disordered Proteins - Zavrtanik, Uroš; Hadži, San; Lah, Jurij (Frontiers in Molecular Biosciences, 2021)
Protein interactions mediated by the intrinsically disordered proteins (IDPs) are generally associated with lower affinities compared to those between globular proteins. Here, we characterize the association between the intrinsically disordered HigA2 antitoxin and its globular target HigB2 toxin from Vibrio cholerae using competition ITC experiments. We demonstrate that this interaction reaches one of the highest affinities reported for IDP-target systems (KD = 3 pM) and can be entirely attributed to a short, 20-residue-long interaction motif that folds into α-helix upon binding. We perform an experimentally based decomposition of the IDP-target association parameters into folding and binding contributions, which allows a direct comparison of the binding contribution with those from globular ultra-high affinity binders. We find that the HigA2-HigB2 interface is energy optimized to a similar extent as the interfaces of globular ultra-high affinity complexes, such as barnase-barstar. Evaluation of other ultra-high affinity IDP-target systems shows that a strategy based on entropy optimization can also achieve comparably high, picomolar affinities. Taken together, these examples show how IDP-target interactions achieve picomolar affinities either through enthalpy optimization (HigA2-HigB2), resembling the ultra-high affinity binding of globular proteins, or via bound-state fuzziness and entropy optimization (CcdA-CcdB, histone H1-prothymosin α).